2016
DOI: 10.1002/2015jd023895
|View full text |Cite
|
Sign up to set email alerts
|

Using data insertion with the NAME model to simulate the 8 May 2010 Eyjafjallajökull volcanic ash cloud

Abstract: A data insertion method, where a dispersion model is initialized from ash properties derived from a series of satellite observations, is used to model the 8 May 2010 Eyjafjallajökull volcanic ash cloud which extended from Iceland to northern Spain. We also briefly discuss the application of this method to the April 2010 phase of the Eyjafjallajökull eruption and the May 2011 Grímsvötn eruption. An advantage of this method is that very little knowledge about the eruption itself is required because some of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 60 publications
1
60
0
Order By: Relevance
“…A better source term for the entire episode studied may be found by assimilating several satellite observations over the entire period studied. Wilkins et al (2016a) used an insertion method for ash forecasting by initializing a dispersion model with ash layers derived from retrievals of the Spinning Enhanced Visible and Infrared Imager (SEVIRI) on board the Meteosat Second Generation (MSG-2) satellite. The study found that the model field calculated by including up to six satellite observations gave a broader and more extensive ash cloud, which compared worse to the satellite observation on 8 May at 09:00 UTC than a single satellite retrieval inserted 6 h before the observation time.…”
Section: Introductionmentioning
confidence: 99%
“…A better source term for the entire episode studied may be found by assimilating several satellite observations over the entire period studied. Wilkins et al (2016a) used an insertion method for ash forecasting by initializing a dispersion model with ash layers derived from retrievals of the Spinning Enhanced Visible and Infrared Imager (SEVIRI) on board the Meteosat Second Generation (MSG-2) satellite. The study found that the model field calculated by including up to six satellite observations gave a broader and more extensive ash cloud, which compared worse to the satellite observation on 8 May at 09:00 UTC than a single satellite retrieval inserted 6 h before the observation time.…”
Section: Introductionmentioning
confidence: 99%
“…This metric individually considers aspects of the structure (S), amplitude (A), and location (L) of a forecast, revealing meaningful information about the systematic differences between forecasts. This diagnostic metric has been previously used to measure the skill of volcanic ash forecast using data insertion from 25 satellite observations ( Wilkins et al, 2016) and has been adapted here to compare the quality of on-line and off-line coupled NMMB-MONARCH-ASH forecasts. …”
Section: Quantitative Evaluation Scoresmentioning
confidence: 99%
“…Wilkins et al, 2016) to complement the SAL score for the evaluation of the spatial coverage between forecasts:…”
Section: Categorical Evaluation Scoresmentioning
confidence: 99%
“…Another active field for STE applications is the estimation of the volcanic ash emissions. Many attempts have been made for several major volcano eruptions (Wen and Rose, 1994;Prata and Grant, 2001;Wilkins et al, 2014Wilkins et al, , 2016Chai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%